1988
DOI: 10.1016/0014-5793(88)80824-x
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids alter sterol transbilayer domains in LM fibroblast plasma membrane

Abstract: Sterols are asymmetrically distributed between the leaflets of animal cell plasma membranes. Although transbilayer migration of sterols is extremely rapid, s to rain, previous experimental manipulations have not altered their transmembrane steady-state distribution. However, the effect of polyunsaturated fatty acids has not been reported. When cultured in a lipid-free, chemically defined culture medium, LM fibroblasts do not synthesize polyunsaturated fatty acids but will incorporate polyunsaturated fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 49 publications
(55 reference statements)
2
19
0
Order By: Relevance
“…However, very rapid cholesterol flip-flop [138,139] makes precise cholesterol asymmetry measurements difficult. Upon addition of PUFA in culture, a decrease in molecular order and a redistribution of cholesterol with more than 70% going to the outer leaflet was reported by Schroeder and co-workers [132,133]. Dusserre et al [140] reported cholesterol efflux from plasma membranes remained the same after incorporation of oleate, linoleate or arachidonate but increased with EPA and DHA.…”
Section: Dha and Membrane Domainsmentioning
confidence: 86%
See 1 more Smart Citation
“…However, very rapid cholesterol flip-flop [138,139] makes precise cholesterol asymmetry measurements difficult. Upon addition of PUFA in culture, a decrease in molecular order and a redistribution of cholesterol with more than 70% going to the outer leaflet was reported by Schroeder and co-workers [132,133]. Dusserre et al [140] reported cholesterol efflux from plasma membranes remained the same after incorporation of oleate, linoleate or arachidonate but increased with EPA and DHA.…”
Section: Dha and Membrane Domainsmentioning
confidence: 86%
“…Addition of PUFA to membranes has also been shown to alter trans-bilayer sterol localization [132,133]. Although the transmembrane distribution of cholesterol is not known with absolute certainty [134,135], the outer leaflet of plasma membranes may contain more cholesterol and therefore be more rigid than the inner leaflet.…”
Section: Dha and Membrane Domainsmentioning
confidence: 99%
“…Firstly, the exofacial and cytofacial leaflets of the plasmalemma differ in phospholipid headgroup composition, cholesterol content as well as fatty acid composition, and this nonsymmetric composition results in a transbilayer fluidity gradient regulated largely by unsaturated fatty acids (Kier et al, 1986;Sweet and Schroeder, 1988b). Secondly, the plasmalemma also contains lateral domains (lipid rafts/caveolae as well as non-raft domains) that differ in their lipid composition and protein distribution (for reviews, see Pike, 2003;Pike et al, 2002;Schroeder et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…in (12,144,145). DHE revealed that the cytofacial leaflet of plasma membranes from L-cell fibroblasts (12,24,146,147), erythrocytes (144), and brain synaptosomes (145,(148)(149)(150)(151). While other methods (filipin staining, exchange, cholesterol oxidase accessibility, neutron diffraction, etc) have also been used to measure transbilayer cholesterol distribution, many have significant limitations including accessibility of membrane cholesterol (filipin, cholesterol oxidase), production of a potential perturbant (cholesterol oxidase produces cholesterone), and poor dynamic resolution (neutron diffraction) (rev.…”
Section: Dhe Architecture In Purified Biological Membranesmentioning
confidence: 99%
“…The transbilayer distribution of sterol is a major determinant of the transbilayer fluidity gradient present in these membranes, the cytofacial cholesterol-rich leaflet is more rigid (less fluid) than the relatively cholesterol-poor exofacial leaflet (rev. in (146,147,149,(153)(154)(155)(156)(157)(158)(159). The transbilayer migration rate of DHE in model membranes and plasma membranes is relatively fast, t 1/2 of sec-min depending on the membrane examined (rev.…”
Section: Dhe Architecture In Purified Biological Membranesmentioning
confidence: 99%